The Relationship Between Social Interaction and the Quality of Life of the Elderly at the Jannati Nursing Home in Gorontalo Province - Euis Herawati Hidayat; Sabirin B. Syukur; Devina Tesya Latama (PROMOTOR, 2024)
Social interaction is a relationship between two or more people in the form of communication or social contact that results in answering each other, social interaction will affect the quality of life of the elderly in the panti. Quality of life is a perception of life that is being carried out by the culture and values in which the individual lives and compares his life with the goals, expectations, standards, and goals set by the individual. The purpose of the study was to determine the relationship between social interaction and the quality of life of the elderly—a quantitative research design with a cross-sectional approach. The population is 30 respondents or a total sampling. The results showed that the social interaction category was less with quality of life obtained respectively for the less 2 respondents (6.7%), and the moderate 2 respondents (6.7%). Social interaction is sufficient with less quality of life for as many as 2 respondents (6.7%). Good category social interaction with good quality of life as many as 24 respondents (80%) with p-value = 0.00 < 0.05. Advice as information to the orphanage ship and its staff regarding the benefits of social interaction to improve the quality of life of the elderly.